Hybrid Computational Near-Eye Light Field Display - Jian Zhao; Qungang Ma; Jun Xia; Jun Wu; Bintao Du; Hao Zhang (IEEE Photonics Journal, 2019)
We propose a hybrid computational near-eye light field display based on micro-lens arrays (MLAs) and structure parameters prioritization method (SPPM) that can render correct accommodation and expand the depth of field (DOF). The proposed display consists of two MLAs and two micro-displays. Two sets of depth-sliced images are superimposed to reconstruct the object's light field. The system's ray resolution and the spectra difference between the proposed light field and the conventional one are discussed. The DOF of the proposed system is extended without the requiring of high refresh rate display. Furthermore, SPPM is proposed to extend the spatial frequency of the light field. A prototype is demonstrated and the experimental result shows that the depth field of the reconstructed images is significantly increased compared with conventional near-eye light field display based on single MLA.